Pentingnya Menerapkan Asupan Gizi Seimbang di SD Negeri 12 Kendari Kecamatan Nambo Kota Kendari Provinsi Sulawesi Tenggara Tahun 2025 - Rahman Rahman; Ruslan Majid; Farid Rezal; Rahmiza Hamzah; Nurul Hikmah Ridhayani; Julia Lambe; Poppy Kayla Rivana; Rifdah Molidah; Rossa Aprilia Wulan As’Ad (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The educational activity "Isi Piringku: The Importance of Implementing Balanced Nutritional Intake Daily" was conducted on May 20, 2025, at SD Negeri 12 Kendari with the aim of increasing students' knowledge about balanced nutrition through PowerPoint media. Participants consisted of 22 students aged 9-11 years with 54.5% male and 45.5% female composition. The research method used pre-test and post-test design which showed an increase in average scores from 3.73 (pre-test) to 5.59 (post-test) with p=0.000 (p<0.05), indicating a significant difference in knowledge before and after the educational session. The research results prove that PowerPoint media is effective in increasing students' knowledge about the importance of balanced nutrition and the application of the "Isi Piringku" concept in daily life.